2002
DOI: 10.1080/02692170110118885
|View full text |Cite
|
Sign up to set email alerts
|

Does Financial Development 'Lead' Economic Growth?

Abstract: We use the Toda & Yamamoto (1995) causality testing procedure to investigate the relationship, if any, between financial development and economic growth.We use quarterly data from 19 OECD countries and China, and use total credit and interest spread as indicators of financial development. We also consider the impact of financial development on investment and productivity. We find meagre evidence that financial development 'leads' economic growth, either directly or indirectly. This casts further doubt on claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
111
1
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(135 citation statements)
references
References 21 publications
5
111
1
10
Order By: Relevance
“…Several studies such as Marin [40] , Pomponio [45] , McCarville and Nnadozie [41] , Darat [9] have used the raditional (F-test) to test for causality. The use of a simple traditional Granger causality has been identified by several studies [14,52] as not sufficient if variables are 1(1) and cointegrated. If time series included in the analysis are 1(1) and cointegrated, the traditional Granger causality test should not be used and proper statistical inference can be obtained by analysing the causality relationship on the basis of the error correction model (ECM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies such as Marin [40] , Pomponio [45] , McCarville and Nnadozie [41] , Darat [9] have used the raditional (F-test) to test for causality. The use of a simple traditional Granger causality has been identified by several studies [14,52] as not sufficient if variables are 1(1) and cointegrated. If time series included in the analysis are 1(1) and cointegrated, the traditional Granger causality test should not be used and proper statistical inference can be obtained by analysing the causality relationship on the basis of the error correction model (ECM).…”
Section: Resultsmentioning
confidence: 99%
“…Shan, Morris and Sun [52] use a Granger causality procedure to investigate the relationship between financial development and economic growth for nine OECD countries and China by estimating a vector autoregression (VAR) model. The results of their study show that five out of ten countries have a bilateral Granger causality; three of them have reverse causality with economic growth leading to financial development while two countries do not have a causal effect at all.…”
Section: Introductionmentioning
confidence: 99%
“…King and Levine (1993) concluded that financial development leads economic growth, and Levine and Zervos (1998) found that stockmarket and banking development lead economic growth. In contrast, Arestis and Demetriades (1997), Shan and Morris (2002) and Shan, Sun and Morris (2001) found that the hypothesis was supported in only a few of the countries surveyed and, therefore, that no general conclusions could be drawn.…”
mentioning
confidence: 81%
“…Others, including Sims (1972), Gupta (1984), Jung (1986), Demetriades and Hussein (1996), Demetriades and Luintel (1996), Arestis and Demetriades (1997), Arestis et al (2001) and Shan, Sun and Morris (2001), and Shan and Morris (2002) have used time-series modelling to test the hypothesis. Arestis and Demetriades, in advocating time-series modelling, argued that a cross-sectional approach is based on the implicit assumption that countries have common economic structures and technologies.…”
mentioning
confidence: 99%
“…This proxy has been used extensively in the literature (Majid, 2008;Odedokun, 1996;Shan & Jianhong, 2006;Wood, 1993). …”
Section: Variable Descriptionmentioning
confidence: 99%